The Fentanyl Epidemic and Evolution of Fentanyl Analogs in the United States and the European Union - Jannetto, Paul J; Helander, Anders; Garg, Uttam; Janis, Gregory C; Goldberger, Bruce; Ketha, Hemamalini (Clinical chemistry (Baltimore, Md.), 2019)
Since 2013, an unprecedented surge in fentanyl overdose deaths has been caused by heroin laced with illicitly produced fentanyl and/or fentanyl analogs (FAs) sold as heroin. The US Drug Enforcement Agency's National Forensic Laboratory Information System reported a >300% increase in fentanyl encounters from 4697 in 2014 to 14440 in 2015. In 2015, the CDC reported 9580 deaths caused by synthetic opioids, primarily fentanyl, a 72% increase from 2014. The European Monitoring Centre for Drugs and Drug Addiction has also encountered several new FAs in the heroin supply. Counterfeit pharmaceuticals containing mixtures of fentanyl and FAs continue to be a poorly recognized worldwide problem despite the WHO classifying several FAs as a serious threat to public health. This review covers the epidemiology of fentanyl abuse and discusses the clinical practice implications of widespread fentanyl abuse. It includes a historical perspective on the illicit FAs that have appeared in the US and European Union and reviews the methods available to identify FAs and emerging technologies useful for identifying previously undescribed analogs. A compilation of structural and mass spectral data on FAs reported thus far is provided. Fentanyl and FAs have evolved into a global public health threat. It is important to understand the analytical, clinical, and regulatory efforts underway to assist communities affected by the current fentanyl epidemic.